Jujuboside B Reverse CUMS-Promoted Tumor Progression via Blocking PI3K/Akt and MAPK/ERK and Dephosphorylating CREB Signaling - Zhen Yang; Weijia Cai; Yitian Chen; Zhijun Guo; Zhijun Xiao; Ting Zhou; Yuanchi Cheng; Feng Xu (Journal of Immunology Research)
Background. Jujuboside B (JUB) is a saponins isolated from the seeds of Zizyphi jujuba var. spinosi, which is used to treat mental illness and is reported recently to induce cancer cell apoptosis. As our previous research showed chronic stress promoted tumor growth, this work aims to investigate whether JUB exert antitumor effect in addition to its antidepressant effect and possible mechanism. Methods. 56 female C57BL/6 mice were grouped into 7 groups: A (blank control), B (tumor-bearing control), C (tumor-bearing + JUB), D (CUMS control), E (CUMS + JUB), F (tumor-bearing + CUMS), and G (tumor-bearing + CUMS + JUB). Groups C, E, G, B, D, and F were administered, respectively, with JUB (40 mg/kg/day) or vehicle for 2 weeks. Serum 5-HT, Trp (tryptophane), inflammatory cytokines TNF-α, IL-4, -6, and -10 levels were detected by ELISA. The tumors in groups B and F were isolated for RNA-seq sequencing. Protein and mRNA expression of Bax, Bcl-2, p-PI3K, p-Akt, p-MAPK, p-ERK, and p-CREB in tumor tissues were detected. In vitro, A549 cells were stimulated with JUB (60 μmol/L), in which proliferation rate and colony formation rate were detected. The PI3K/Akt and, MAPK/ERK pathway were measured. Results. Chronic stress successfully induced the depression-like phenotype (group D vs. A) and promoted tumor growth (group B vs. F). JUB significantly ameliorated the depression-like phenotype and increased 5-HT, Trp levels (group D vs. E), and reversing CUMS-induced tumor progression. Meanwhile, JUB decreased inflammatory cytokine levels. Chronic stress upregulated the phosphorylation levels of PI3K/Akt/MAPK/ERK/CREB; JUB reversed this regulation. JUB significantly inhibited cell viability, colony formation rate, and downregulated the phosphorylation levels of PI3K/Akt/MAPK/ERK/CREB in vitro. Conclusions. JUB reverses CUMS-promoted tumor progression in tumor-bearing mice with depression-like phenotype. JUB exerts the dual beneficial effect on tumor growth and depression-like phenotype by blocking the signal transduction pathway of PI3K/Akt, MAPK/ERK, and dephosphorylating the downstream signaling regulator CREB.